2013
DOI: 10.1080/17524032.2013.810164
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Barriers to Successful Environmental Advocacy Campaigns in the Organizational Context

Abstract: This paper extends the scope of environmental communication studies from the public sphere to the organizational context with two main aims: first, to understand what barriers there are to individual environmental behavior and second, to suggest how these barriers can be overcome. The findings, based on 13 interviews in Finnish organizations that have implemented an environmental advocacy campaign, the WWF Green Office, support previous findings on individual and societal barriers and, in addition, suggest fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The study identified five main challenges in implementing green practices in office building, namely lack of budget, lack of awareness, lack of expertise, rented office, and building type. While lack of budget, lack of awareness, and lack of expertise challenges are in agreement with prior studies (see Esa, 2011;Goh, 2013;Masrom, 2017;Samari, 2013;Shafii, 2006;Uusi-Rauva & Heikkurinen, 2013), this study contributes to the literature by identifying rented office and building type factors as new challenges according to the experience of building owners. Therefore, the findings provide new insights regarding the challenges of implementing a green office in Penang.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The study identified five main challenges in implementing green practices in office building, namely lack of budget, lack of awareness, lack of expertise, rented office, and building type. While lack of budget, lack of awareness, and lack of expertise challenges are in agreement with prior studies (see Esa, 2011;Goh, 2013;Masrom, 2017;Samari, 2013;Shafii, 2006;Uusi-Rauva & Heikkurinen, 2013), this study contributes to the literature by identifying rented office and building type factors as new challenges according to the experience of building owners. Therefore, the findings provide new insights regarding the challenges of implementing a green office in Penang.…”
Section: Discussionsupporting
confidence: 84%
“…Most of these articles were related to the engineering field (21 articles) with the main focus on indoor environmental quality (see Elnaklah, Fosas, & Natarajan, 2020;Lin, Liu, Wang, Pei, & Davies, 2016) and energy consumption (see Geng, Lin, & Zhu, 2020;Yau & Lim, 2016;Zhou, Cai, & Xu, 2020). Screening of abstracts resulted in only five articles related to challenges in green office implementation with three articles focusing on developed countries (see Adomßent, Grahl, & Spira, 2019;Pulaski & Horman, 2005;Uusi-Rauva & Heikkurinen, 2013), while the rest were from China with a narrow focus on green rating (Zuo, Xia, Chen, Pullen, & Skitmore, 2016) and office interior (Gou, 2016). Clearly, more studies are in need to identify the challenges of implementing green office within the context of Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…That is, in contrast to civil society-based environmental movements struggling against public or private organizations in calls for wholesale changes, ‘green inside activism’ concerns changing these (often large) institutions incrementally from within. This can directly involve transnational environmental activist groups, as they collaborate closely with state institutions and corporate organizations (Dahan, Doh, Oetzel, & Yaziji, 2010; Wapner, 1996), as in WWF’s Green Office programme, where organizational members have been empowered to act pro-environmentally (Uusi-Rauva & Heikkurinen, 2013).…”
Section: Activism and Politics In Organization Studiesmentioning
confidence: 99%
“…Others, however, have been critical of modest and incremental approaches to behavior modification in light of climate change, suggesting that it may prevent greater actions by encouraging consumers to "rest on [their] laurels" (Thøgersen & Crompton, 2009, p. 150). Finally, it should be mentioned that fostering environmental behavior within organizations is a distinct challenge in itself (Uusi-Rauva & Heikkurinen, 2013), and that internal organizational factors may also have an impact on the selection of messages by NGO staff members.…”
Section: Prior Research On Meat and Messaging Choicesmentioning
confidence: 99%
“…NGOs where the majority of staffers eat meat, particularly beef, may wish to engage in a reflective process where they consider to what extent their own personal opinions and preferences relating to meat consumption have shaped their campaigns and messages aimed at altering meat consumption in light of climate change. It should be noted, however, that there are multiple barriers to fostering environmental behavior within organizations and that this may represent a challenge in and of itself (Uusi-Rauva & Heikkurinen, 2013).…”
Section: Staffers' Own Willingness To Change Impacts Messagingmentioning
confidence: 99%